LncRNA Functions as a New Emerging Epigenetic Factor in Determining the Fate of Stem Cells - Chen, Jingcheng; Wang, Yizhuo; Wang, Cong; Hu, Ji-Fan; Li, Wei (Frontiers in Genetics, 2020)
Pluripotent stem cells have broad applications in regenerative medicine and offer ideal models for understanding the biological process of embryonic development and specific diseases. Studies suggest that the self-renewal and multi-lineage differentiation of stem cells are regulated by a complex network consisting of transcription factors, chromatin regulators, signaling factors, and noncoding RNAs. It is of great interest to identify RNA regulatory factors that determine the fate of stem cells. Long noncoding RNA (lncRNA), a calss of noncoding RNAs with more than 200 bp in length, has been shown to act as essential epigenetic regulators of stem cell pluripotency and specific lineage commitment. In this review, we focus on recent research progress related to the function and epigenetic mechanisms of lncRNA in determining the fate of stem cells, particularly pluripotency maintenance and lineage-specific differentiation. We discuss the role of the Oct4 and Sox2 promoter-interacting lncRNA as identified by Chromatin RNA In Situ reverse Transcription sequencing (CRIST-seq). Further understanding of their potential actions will provide a basis for the development of regenerative medicine for clinical application. This work offers comprehensive details and better understanding of the role of lncRNA in determining the fate of stem cells and paves the way for clinical stem cell applications.